Novel [4-Hydroxy-TEMPO + NaCl]/SiO2 as a Reusable Catalyst for Aerobic Oxidation of Alcohols to Carbonyls - Tamura, Naoya; Aoyama, Tadashi; Takido, Toshio; Kodomari, Mitsuo (Synlett, 2012)
A convenient method for the preparation of [4-hydroxy-TEMPO + NaCl]/SiO2 was developed. And [4-hydroxy-TEMPO + NaCl]/SiO2 with Fe(NO3)3·9H2O was used for an aerobic oxidation of alcohols to carbonyls under mild reaction conditions. Alcohols were converted to the corresponding carbonyls in good to excellent yields. [4-Hydroxy-TEMPO + NaCl]/SiO2 can be easily separated from the reaction mixture by filtration and reused at least six times.
Keywords: alcohols; TEMPO; oxidation; supported catalyst; ketones